A Novel Laryngeal Preservation Technique following Total Glossectomy with Hyoid Bone Resection - Koreyuki Kurosawa, MD; Takayuki Imai, MD; Ko Matsumoto, MD; Yukinori Asada, MD; Kengo Katoh, MD; Kazuto Matsuura, MD; Takahiro Goto, MD (Plastic and Reconstructive Surgery, Global Open, 2018)
Summary:. Despite the recent progress of chemotherapy and sophisticated radiotherapy, surgery still remains the most reliable treatment for advanced tongue cancers in terms of survival. The major disadvantage of this treatment is that it should sacrifice the quality of patients’ life. When the tongue cancer is so advanced as to involve the hyoid bone, which is considered a functional part of the larynx, radical operation needs to resect both the entire tongue and the larynx and the hyoid bone en bloc to prevent aspiration pneumonia. As a result of total laryngectomy, the patients will suffer significant disabilities: aphonia and the loss of deglutition that limits the oral intake to only liquid or pasty food. With this clinical background, we have been contriving to overcome these significant surgical shortcomings by conducting larynx-preserving operation. In this case report, we present our newly devised surgical method which consists of free-flap transfer with a combination of laryngeal suspension and a novel reconstructive technique, that is, epiglottis suspension, which enabled favorable swallowing function without aspiration and allowed a sufficiently wide airway for breathing. The operation worked quite successfully for the patient’s quality of life. We believe this novel surgical method would serve as a larynx-preservation treatment for locally advanced tongue cancers with hyoid bone invasion.